2014
DOI: 10.1373/clinchem.2013.216978
|View full text |Cite
|
Sign up to set email alerts
|

Weekly and 90-Minute Biological Variations in Cardiac Troponin T and Cardiac Troponin I in Hemodialysis Patients and Healthy Controls

Abstract: BACKGROUND:Myocardial infarction (MI) is diagnosed by the finding of a single cardiac troponin value above the 99th percentile and a significant time-dependent change in cardiac troponin concentration. The aim of this study was to determine the 90-min and weekly biological variations, the reference change value (RCV), and the index of individuality (II) of high-sensitivity cardiac troponin T (hs-cTnT) (Roche Diagnostics) and hs-cTnI (Abbott Diagnostics) in patients receiving hemodialysis (HD) and in healthy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
70
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 36 publications
13
70
0
8
Order By: Relevance
“…Our estimates of the within-person variation of hs-cTnT in the dialysis population are supported by the findings of Aakre et al [32], Pianta et al [16] and Jacobs et al [33] who reported a within-person coefficient of variation of 8.3%, 9.7% and 13% for hs-cTnT measured weekly, fortnightly and monthly, respectively, in haemodialysis patients. However, these studies were limited by the exclusion of peritoneal dialysis patients [16,32,33], a paucity of repeated measures [16,33] and most importantly by a lack of rigour in ensuring patient stability, wherein they relied either on patient report [16] or a history of hospitalisation [32,33] trend; this may reflect recovering acute myocardial injury due to haemodialysis-induced cardiac stunning [34] which was not considered by the authors [32].…”
Section: Strengths and Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…Our estimates of the within-person variation of hs-cTnT in the dialysis population are supported by the findings of Aakre et al [32], Pianta et al [16] and Jacobs et al [33] who reported a within-person coefficient of variation of 8.3%, 9.7% and 13% for hs-cTnT measured weekly, fortnightly and monthly, respectively, in haemodialysis patients. However, these studies were limited by the exclusion of peritoneal dialysis patients [16,32,33], a paucity of repeated measures [16,33] and most importantly by a lack of rigour in ensuring patient stability, wherein they relied either on patient report [16] or a history of hospitalisation [32,33] trend; this may reflect recovering acute myocardial injury due to haemodialysis-induced cardiac stunning [34] which was not considered by the authors [32].…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…However, these studies were limited by the exclusion of peritoneal dialysis patients [16,32,33], a paucity of repeated measures [16,33] and most importantly by a lack of rigour in ensuring patient stability, wherein they relied either on patient report [16] or a history of hospitalisation [32,33] trend; this may reflect recovering acute myocardial injury due to haemodialysis-induced cardiac stunning [34] which was not considered by the authors [32].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Barring intra-and inter-day variability, baseline cTn levels are relatively stable and change only slowly with time [28,59,77,78]. Hs assays allow establishing each person's baseline cTn levels.…”
Section: Additional Considerations In Diagnosing Amimentioning
confidence: 99%
“…In a stable ESRD population, 50% to 90% of high-sensitivity cardiac troponin T (hs-cTnT) concentrations are above the 99th percentile upper reference limit (URL) compared to Ͻ25% for hs-cTnI assays (11 ). Using serial hs-cardiac troponin changes over time as a risk-stratification approach in HD or ESRD patients has not been addressed (12,13 ).…”
Section: Hemodialysis (Hd)mentioning
confidence: 99%